Community treatment orders: learning from experiences of service users, practitioners and nearest relatives. (April 2015) - Stroud, Julia; Banks, Laura; Doughty, Karolina
Abstract Background: The effectiveness of Community Treatment Orders (CTOs) has been examined previously. However, few studies have explored the significance of service user and practitioner understandings. Aims: The study explored the experiences of service users, practitioners and nearest relatives, to identify key factors and good practice in relation to CTOs. Method: A study of CTOs in a mental health NHS Trust in Southern England, including 72 semi-structured interviews, analysed thematically. Results: CTOs were perceived as helpful in certain circumstances for the "right" service user. Factors influencing effectiveness included recognition of the containing elements of the CTO, a respect for its legal authority and an acceptance of conditions. Conclusions: The perceptions of service users have an important role in determining the value and potential effectiveness of CTOs. A consideration of these issues should be integral to the process of assessing whether a CTO is appropriate in individual cases.